Removal of Iron (Iii) Ion from Aqueous Solution using Polyacrylic Acid Hydorgel Beads as Adsorbent - Al-Abachi, Mouayad; Al- Awady, Nagam; Al- Anbakey, Ahmed (Iraqi Journal of Science, 2024)
This research focuses on the removal and adsorption of Fe (III) ion using a low cost commercial polyacrylic acid hydrogel beads as adsorbent. The effects of time, initial concentration and pH on the metal ion adsorption capacity were investigated. The regeneration of the hydrogel bead and recovery of the metal ion adsorbed were study. The adsorption isotherm models were applied on experimental data and it is shown that the Langmuir model was the best one for Fe (III) ion removal. The maximum capacity was calculated. First-order and second- order kinetic models were used and it is shown that the experimental data was in reliable compliance with the first- order model with R2 value of (0.9935, 0.9011, 0.9695, 0.9912) for all concentrations which were used in this study (100, 200, 300, 400) mg.L-1 respectively.